2023
DOI: 10.1093/stcltm/szad010
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B Cells Contribute to the Clinical Response After Bone Marrow-Derived Mesenchymal Stromal Cell Infusion in Patients With Systemic Sclerosis

Abstract: Mesenchymal stromal cells (MSCs) have recently emerged as an interesting therapeutic approach for patients with progressive systemic sclerosis (SSc), a rare and life-threatening orphan autoimmune disease. Whereas MSC immunomodulatory potential is considered as a central mechanism for their clinical benefit, very few data are available on the impact of MSCs on immune cell subsets in vivo. In the current extended study of a phase I/II clinical trial exploring the injection of a single dose of allogeneic bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…The SSc vascular damage is characterized by the presence of a characteristic processes with a vasomotor instability with an imbalance of vasoactive factors: overproduction of vasoconstrictors (ET-1) and underproduction of vasodilators (NO and prostacyclin) [6][7][8][9][10][11][12][13][22][23][24][25][106][107][108][109]. The free radical nitric oxide (NO) is a potent vasodilator and is synthesized from L-arginine by NO synthase (NOS) [10][11][12][13][14][15][16][17][18][19][22][23][24][25][40][41][42][43][44][45][46][47][48][106][107][108][109][110][111][112][113]. Endothelial isoforms of NOS (eNOS or NOS 3) has been identified with a constitutive expression, other isoforms are shown...…”
Section: The Role Of Endothelial Injury In Systemic Sclerosis Pathoge...mentioning
confidence: 99%
See 4 more Smart Citations
“…The SSc vascular damage is characterized by the presence of a characteristic processes with a vasomotor instability with an imbalance of vasoactive factors: overproduction of vasoconstrictors (ET-1) and underproduction of vasodilators (NO and prostacyclin) [6][7][8][9][10][11][12][13][22][23][24][25][106][107][108][109]. The free radical nitric oxide (NO) is a potent vasodilator and is synthesized from L-arginine by NO synthase (NOS) [10][11][12][13][14][15][16][17][18][19][22][23][24][25][40][41][42][43][44][45][46][47][48][106][107][108][109][110][111][112][113]. Endothelial isoforms of NOS (eNOS or NOS 3) has been identified with a constitutive expression, other isoforms are shown...…”
Section: The Role Of Endothelial Injury In Systemic Sclerosis Pathoge...mentioning
confidence: 99%
“…Endothelial isoforms of NOS (eNOS or NOS 3) has been identified with a constitutive expression, other isoforms are shown in other cell types. Furthermore, an inducible expression (iNOS or NOS 2) in response to a variety of stimuli is possible, with NO-mediated signalling apparent in the skin [10][11][12][13][14][15][16][17][18][19][40][41][42][43][44][45][46][47][48][106][107][108][109][110][111][112][113]. Several studies reported that NO have a biphasic effect in physiological and pathological conditions, being both beneficial and detrimental depending on the concentration and local environment [10][11][12][13][14][15][16][17][18][19][40][41][42][43][44][45][46][47][48].…”
Section: The Role Of Endothelial Injury In Systemic Sclerosis Pathoge...mentioning
confidence: 99%
See 3 more Smart Citations